PERLINDUNGAN HUKUM TERHADAP TANAH ULAYAT YANG TELAH BERSERTIFIKAT DI KOTA BUKITTINGGI - Nova Yarsina (STIH Putri Maharaja, 2018)
Registration of land which its perpetrators by Law Number 5 Year 1960 assigned to the Government is a means of providing legal certainty in the field of land and for the implementation of the orderliness of land administration PP Number 24 of 1997, then every plot of land and apartment units must be registered. In view of the provisions of Articles 1 and 2PP of the customary rights and similar rights of customary law communities, to the extent they are in fact still exist, should be like that in accordance with national and state interests, based on national unity and may be contrary to other laws and other regulations. This research was field research that is field research with interview technique to related parties that directly related to problem which writer discuss. This research was included in the type of qualitative research. Based on the research that has been done the authors can conclude that the absence of legal protection of Ulayat land that has been certified Ulayat land is not a right that can be registered, there is only recognition, so it is not a right that can be registered. Toward the land which has been registered has disappeared its owner meaning, where the land has changed into a common property (mede aigendom), as if they have a common right, the position of men and women about the right of inheritance of the same high haritage and parallel.